Implementasi Persiapan Perkawinan di Paroki Bunda Hati Kudus Woloan - Johanes Danny Surentu; Shefry Yanny Fransisco Topit (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
The preparation of marriage should be carried out in a gradual and continuous process, which must be given by the Shepherd of souls in the form of sermons and catechesis adapted from childhood, youth, and adulthood. However, according to initial observations made, researchers saw that in the Parish of Our Lady of the Sacred Heart of Woloan, marriage preparations are only given to people who have reported holding a wedding celebration. This encourages researchers to know and describe people's understanding of marriage preparation, describe the implementation of marriage preparation in the Parish of Mother of the Sacred Heart of Woloan, and describe efforts to improve the effectiveness of marriage preparation in the Parish of Mother of the Sacred Heart of Woloan. This research uses a type of descriptive research with a qualitative approach.  The research techniques used for this study were observation, interviews, and documentation. The data sources are the marriage preparation team, prospective married couples, and married couples in the Parish of Our Lady of the Sacred Heart of Woloan. From the results of the research obtained, theresearchers concluded that marriage preparation is an initial process that must be taken by prospective married couples to get to know each other's duties and responsibilities as husband and wife, and understand what agreement they will build. In addition, in its application of the 3 forms of marriage preparation listed in the Apostolic Advice Familiaris Consortio number 66, namely far preparation, and close preparation, only 1 is applied in Woloan Parish, namely direct marriage preparation (preparatio directa). Therefore, in order to improve the effectiveness of marriage preparation, things such as improving the quality of the marriage preparation team, socialization about distant preparation, trying to procure close preparation courses, and always holding evaluation meetings for the marriage preparation team need to be done.